Long-Term Management of Palmer Amaranth (Amaranthus palmeri) in Dicamba-Tolerant Cotton. Issue 1 (March 2016) - Inman, Matthew D.; Jordan, David L.; York, Alan C.; Jennings, Katie M.; Monks, David W.; Everman, Wesley J.; Bollman, Scott L.; Fowler, John T.; Cole, Richard M.; Soteres, John K.
Abstract : Research was conducted from 2011 to 2014 to determine weed population dynamics and frequency of glyphosate-resistant (GR) Palmer amaranth with herbicide programs consisting of glyphosate, dicamba, and residual herbicides in dicamba-tolerant cotton. Five treatments were maintained in the same plots over the duration of the experiment: three sequential POST applications of glyphosate with or without pendimethalin plus diuron PRE; three sequential POST applications of glyphosate plus dicamba with and without the PRE herbicides; and a POST application of glyphosate plus dicamba plus acetochlor followed by one or two POST applications of glyphosate plus dicamba without PRE herbicides. Additional treatments included alternating years with three sequential POST applications of glyphosate only and glyphosate plus dicamba POST with and without PRE herbicides. The greatest population of Palmer amaranth was observed when glyphosate was the only POST herbicide throughout the experiment. Although diuron plus pendimethalin PRE in a program with only glyphosate POST improved control during the first 2 yr, these herbicides were ineffective by the final 2 yr on the basis of weed counts from soil cores. The lowest population of Palmer amaranth was observed when glyphosate plus dicamba were applied regardless of PRE herbicides or inclusion of acetochlor POST. Frequency of GR Palmer amaranth was 8% or less when the experiment was initiated. Frequency of GR Palmer amaranth varied by herbicide program during 2012 but was similar among all herbicide programs in 2013 and 2014. Similar frequency of GR Palmer amaranth across all treatments at the end of the experiment most likely resulted from pollen movement from Palmer amaranth treated with glyphosate only to any surviving female plants regardless of PRE or POST treatment. These data suggest that GR Palmer amaranth can be controlled by dicamba and that dicamba is an effective alternative mode of action to glyphosate in fields where GR Palmer amaranth exists.